PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA KULIAH TEORI DAN PRAKTIK PLAMBING DI PROGRAM STUDI S1 PVKB UNJ - Nanda Dewi; R. Eka Murtinugraha; Riyan Arthur (Jurnal Pensil : Pendidikan Teknik Sipil, 2018)
This study is a development research that aims to develop an interactive learning media for concept and practice of Plumbing subject using Adobe Flash CS6. This development research was using Borg & Gallâ€™s model. This research using questionnaire as data collection instrument feasibility of the media through the validation by media experts, material expert and student assesment who join concept and practice of plumbing subject. The results of validation learning media with the percentage feasibility 72,92% are in the â€œFeasibleâ€ category, the result of validation by material expert with the percentage feasibility 86,90% are in the â€œVery Feasibleâ€ category and students assesment with the percentage feasibility 82,07% are in the â€œVery Feasibleâ€ category. Based on the results of the above, this developed media learning feasible to be used in concept and practice of Plumbing subject in Vocational Education of Building Construction.